The Enhancement of Teacher Competency Through Assistance in Creating Augmented Reality-Based Interactive E-Modules at SMAN 10 Palembang - Ida Sriyanti; Leni Marlina; Agung Mataram; Muhammad Rudi Sanjaya; Selvia Mariska Syahputri; Rahma Dani; Muhammad Rama Almafie (Unram Journal of Community Service, 2025)
Educational transformation in the Industrial Revolution 4.0 era demands that teachers adapt to digital technology and develop innovation-based learning. However, the results of a preliminary survey indicated that a majority of teachers at SMAN 10 Palembang lacked skills in creating digital learning media and were unfamiliar with Augmented Reality (AR) technology. This community service activity aimed to improve teacher competence through mentoring in the creation of AR-based interactive e-modules as a 21st-century learning innovation. The implementation methods included socialization, technical training, a coaching clinic, and an evaluation of outcomes using a pre-test, post-test, and a participant satisfaction survey. Fifteen teachers actively participated in this activity. The paired sample t-test analysis revealed a significant increase between the pre-test (M = 47.00; SD = 7.75) and post-test scores (M = 91.67; SD = 4,87), with t = –18.506, p = 0.000 (p < 0.05). And the Cohen’s d = 9.35, categorized as a very large effect. This finding demonstrates that the mentoring program was effective in enhancing teacher competence in developing AR-based interactive e-modules. Furthermore, the results of the participant satisfaction survey reinforced the program's effectiveness. A total of 73.3% of participants stated they were "very satisfied" with the quality of the mentoring and facilitators, while 80% felt their e-module creation skills had significantly increased. Regarding the AR integration aspect, 87% of participants expressed high satisfaction with the clarity of the training and the implementation results. Meanwhile, 67% rated the activity as having a direct impact on enhancing their instructional technology integration skills. All participants demonstrated a high commitment to sustainably implementing the training outcomes in their respective schools. Consequently, this program is proven to have a positive impact on enhancing digital literacy, pedagogical competence, and teacher readiness to face the challenges of 21st-century, technology-based learning.